Study of Fasting Lipid Profile in Patients with Subclinical Hypothyroidism in a Tertiary Care Hospital in Bangladesh (Faridpur Medical College Journal, 2021)
Subclinical hypothyroidism (SCH) is a metabolic disorder with prevalence about 4-10% in general population. This study was conducted to observe the pattern of fasting lipid profile in SCH and to correlate the components of it with thyroid stimulating hormone and free thyroxin level. This cross sectional observational study included 31 newly diagnosed cases of SCH and 17 age and BMI matched healthy control subjects with normal thyroid function test. Fasting lipid profile was recorded and compared. TSH was significantly higher in SCH compared to controls (9.09±2.79 vs 2.31±0.92 μIU/ml; p=0.001). FT4 was comparable between the groups (1.17±0.18 vs 1.28±0.20 ng/dl; p=0.938). Significantly higher level of Total cholesterol and LDL-C were observed in SCH compared to controls (TC 194.77±29.70 vs 156.59±20.45 mg/dl; p=0.042 and LDL-C 124.81±27.85 mg/dl vs 88.59±18.41mg/dl; p=0.045 respectively). Triglycerides and HDL-C were comparable between the groups (TG 134.90±80.97 vs 118.12±49.14 mg/dl; p=0.171 and HDL-C 42.87±4.83 vs 44.47±5.66; p=0.633 respectively). TSH showed significant positive correlation with TC and LDL-C (r=0.591, p